2017
DOI: 10.21037/jtd.2017.03.24
|View full text |Cite
|
Sign up to set email alerts
|

Early results of the Sorin® Perceval S sutureless valve: systematic review and meta-analysis

Abstract: Background: Minimally invasive aortic valve replacement (MAVR) has demonstrated a benefit with respect to increased patient satisfaction due to minimised pain and earlier recovery. Sutureless valves may benefit MAVR and conventional aortic valve replacement (AVR) by reducing operative times and blood transfusion requirements. The Perceval valve (Sorin, Salluggia, Italy) is a self-expanding prosthesis made from bovine pericardium mounted in a nitinol stent, designed to simplify the implantation of an aortic val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 36 publications
8
24
0
Order By: Relevance
“…Indeed, the rate of permanent pacemaker implantation was lower in the U.S. registry (16.4%, and 19.7% when the patients who had previously received pacemakers were excluded). 1 However, the rate in the SURTAVI trial is similar to that in our study from Geneva (23.9%), 2 a study from Israel (20.4%), 3 and a study from Germany (20.0%) 4 ( Table 1). We think that rates of permanent pacemaker implantation may be influenced by local practice.…”
Section: Doi: 101056/nejmc1706234supporting
confidence: 82%
See 2 more Smart Citations
“…Indeed, the rate of permanent pacemaker implantation was lower in the U.S. registry (16.4%, and 19.7% when the patients who had previously received pacemakers were excluded). 1 However, the rate in the SURTAVI trial is similar to that in our study from Geneva (23.9%), 2 a study from Israel (20.4%), 3 and a study from Germany (20.0%) 4 ( Table 1). We think that rates of permanent pacemaker implantation may be influenced by local practice.…”
Section: Doi: 101056/nejmc1706234supporting
confidence: 82%
“…1,2 Sutureless valves have been introduced into surgical use and appear to provide good hemodynamics but a greater need for new pacemakers and more paravalvular leaks than stented biologic valves, and data on the durability of sutureless valves are lacking. 3 In a randomized trial involving patients who were at high risk for standard surgery, we found that elements of the surgical technique did not influence outcomes. 4 Noble and colleagues emphasize the ongoing, considerable need for permanent pacemakers in patients who undergo TAVR.…”
Section: The Authors Replymentioning
confidence: 92%
See 1 more Smart Citation
“…This case raises the issue of the lack of much-needed data describing the long-term durability and hemodynamic performance of sutureless bioprosthetic valves, particularly in a lowrisk patient with excellent functional status. The SPV was only introduced in 2008 with a total of about 2,500 valves placed to date worldwide [19]. Therefore, the data on long-term durability are scarce to none.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the data on long-term durability are scarce to none. Most of the studies reported shortterm results describing hemodynamic parameters and 30-day outcomes [5,6,16,19,20]. One multicenter study reported 5-year follow-up data and showed favorable hemodynamic parameters such as transaortic valve gradient as well as patient symptomatology [2].…”
Section: Discussionmentioning
confidence: 99%